Application of the Nagoya Protocol to veterinary pathogens: concerns for the control of foot-and-mouth disease - Horsington, Jacquelyn; Abbeloos, Elke; Kassimi, Labib Bakkali; Boonsuya Seeyo, Kingkarn; Capozzo, Alejandra V.; Chepkwony, Eunice; Eblé, Phaedra; Galdo-Novo, Sabrina; Gizaw, Daniel; Gouverneur, Lizelle; Grazioli, Santina; Heath, Livio; et al. (Frontiers in Veterinary Science, 2023)
The Nagoya Protocol is an international agreement adopted in 2010 (and entered into force in 2014) which governs access to genetic resources and the fair and equitable sharing of benefits from their utilisation. The agreement aims to prevent misappropriation of genetic resources and, through benefit sharing, create incentives for the conservation and sustainable use of biological diversity. While the equitable sharing of the benefits arising from the utilisation of genetic resources is a widely accepted concept, the way in which the provisions of the Nagoya Protocol are currently being implemented through national access and benefit-sharing legislation places significant logistical challenges on the control of transboundary livestock diseases such as foot-and-mouth disease (FMD). Delays to access FMD virus isolates from the field disrupt the production of new FMD vaccines and other tailored tools for research, surveillance and outbreak control. These concerns were raised within the FMD Reference Laboratory Network and were explored at a recent multistakeholder meeting hosted by the European Commission for the Control of FMD. The aim of this paper is to promote wider awareness of the Nagoya Protocol, and to highlight its impacts on the regular exchange and utilisation of biological materials collected from clinical cases which underpin FMD research activities, and work to develop new epidemiologically relevant vaccines and other diagnostic tools to control the disease.